Сorrosion and radiation resistance of potassium magnesium phosphate matrices - Sayenko, S.Y.; Shkuropatenko, V.A.; Zykova, A.V.; Surkov, O.Y.; Pylypenko, O.V.; Ulybkina, К.А.; Lobach, K.V. (Вопросы атомной науки и техники, 2018)
Corrosion and radiation resistances of potassium magnesium phosphate (PМP) matrices for hardening of liquid radioactive wastes of NPP were investigated. The high corrosion resistance of the PMP matrices to leaching of both basic components of matrix and cesium was shown. Results of performed work showed stability of physics and mechanical properties, as well as phase composition and microstructure of PMP after simulated γ-irradiation up to the absorbed dose 10⁸ rad. It was determined that irradiation by high-energy electrons to the absorbed dose 10¹⁰ rad results in partial dehydration and amorphization of PMP. Досліджена корозійна та радіаційна стійкість калій-магній-фосфатних (КМФ) матриць для затвердіння рідких радіоактивних відходів АЕС. Показана висока корозійна стійкість КМФ-матриць до вилуговування як основних компонентів матриці, так і цезію. Результати виконаної роботи показали стійкість фізичних та механічних властивостей, а також фазового складу і мікроструктури КМФ після імітації γ-опроміненням до поглиненої дози 10⁸ рад. Було встановлено, що опромінення високоенергетичними електронами до поглиненої дози 10¹⁰ рад призводить до часткової дегідратації та аморфізації КМФ. Исследована коррозионная и радиационная стойкость калий-магний-фосфатных (КМФ) матриц для отверждения жидких радиоактивных отходов АЭС. Показана высокая коррозионная стойкость КМФ-матриц к выщелачиванию как основных компонентов матрицы, так и цезия. Результаты выполненной работы показали устойчивость физических и механических свойств, а также фазового состава и микроструктуры КМФ после имитации γ-облучением до поглощенной дозы 10⁸ рад. Было установлено, что облучение высокоэнергетическими электронами до поглощенной дозы 10¹⁰ рад приводит к частичной дегидратации и аморфизации КМФ.